Feasibility of MEG in assessing task-related oscillatory markers and evaluating cognitive changes in recently symptomatic carotid endarterectomy patients: A pilot study - Tiia Kukkonen; Sanna Liuha; Juha Leukkunen; Hanna-Maija Lapinkero; Ilmari Rouvinen; Simo Monto; Tiina Parviainen (PLoS ONE, 2026)
Revascularization ensures oxygen supply to the brain in patients with significant carotid atherosclerosis. The current indication for carotid endarterectomy (CEA) is stroke risk reduction, but it may also impact cognitive functions and their neural basis. Findings on cognitive outcomes after CEA are inconsistent, and the changes in task-related brain electrophysiology are unknown. In this pilot study, we studied the feasibility of using magnetoencephalography (MEG) to follow the associated brain changes during the first postoperative year in five recently symptomatic CEA patients. Head magnetic resonance imaging (MRI), neuropsychological examinations (NPE), and MEG were performed prior to surgery and repeated twice postoperatively. The stimulus-induced modulation of cortical alpha oscillation changed from pre- to 12 months postoperative recording in simple attention tasks. Neuropsychological examination pointed to improvement in postoperative motor dexterity and working memory. Our tentative results suggest that MEG may provide a useful means to evaluate CEA-related changes in the brain. Additional analyses in larger samples with age-matched controls are required to confirm the link between the changes in brain function and possible improvement in cognitive function in these patients. Increased understanding of the consequences of CEA on brain function and cognition is important both to clinicians and patients.